Report on proposed interior design scheme of education centre for Malaysian Nature Society (MNS) at MZS/Zoo Negara Office,Hulu Kelang,68000 Ampang Selangor / Nur Atikah Mohd Mohsin - Mohd Mohsin, Nur Atikah (Faculty of Architecture, Planning and Surveying, 2011)
Project Report is one of the subject which had to be taken by student part six(06)in Diploma Interior Design in order to graduate. This course provide a practice for student to do their research based on their proposed project and fullfill all the requirement needed. This project report is for a proposed interior design sheme of Education Centre For Malaysian Nature Society (MNS)which form apart of interior design final project. The aim of this education centre is to encourage people either locals or overseas know the importace of Malaysian Nature Society (MNS) and their activities to save the flora fauna in Malaysia.This education centre also creates new indoor environment that tells about the flora fauna to attract people especially kids.Besides that,this education centre can be more Interesting because it is near to the Zoo Negara.At the same time,this education centre can be the annual meeting place for MNS members to discuss or make any campaign or charity event to help the flora fauna project. The Malaysian Nature Society also offer people either locals or overseas be apart of their members.There is a member price rate of different people .On top of that,the design that require by the client is green design perhaps a new modern design but still keep the MNS concept or theme.This education centre will help the Malaysian Nature Society be among and the well known environmental non-government organisation(NGO).